Instructional Design for Competency-Based Character Education in Elementary Schools: A Bibliometric Analysis - Fidelis Dua; Riche Cynthia Johan; Aloysia Berlindis Lasar (Journal of Innovation in Educational and Cultural Research, 2025)
This study uses a bibliometric analysis to examine the trends and impact of instructional design for competency-based character education in elementary schools. Character education plays a crucial role in shaping students' moral and ethical development alongside academic growth. Using data from the Scopus database (2011–2023), this study identifies key publications, authors, institutions, and collaboration networks in this field. A quantitative bibliometric method, employing performance analysis and science mapping, was utilized to evaluate research productivity, citation influence, and keyword trends. Findings reveal an increasing global interest in character education, with Indonesia leading in publication output, followed by Malaysia and the UK. The study highlights the significance of international collaboration, particularly the involvement of Indonesian researchers working abroad. Keyword analysis indicates emerging trends in technology integration, teacher training, and competency-based curriculum development. The study concludes that a structured instructional design is vital in effectively embedding character education within elementary school curricula. This research contributes to the academic discourse by offering a comprehensive bibliometric overview, identifying research gaps, and advocating for stronger international collaborations to enhance character education frameworks. The findings serve as a reference for policymakers, educators, and researchers in designing impactful character education programs.